Українська політична регіоналістика в контексті сучасних суспільно-політичних викликів - Малиновський, Валентин Ярославович; Malynovskyi, Valentyn Ya. (Національний університет "Юридична академія України імені Ярослава Мудрого", 2017)
Суспільно-політичні виклики, що постали перед Україною після Революції гідності у 2014–2017 рр., процеси європейської регіоналізації та децентралізації актуалізували дослідження у сфері політичної регіоналістики. Відповідно, у статті аналізується стан вітчизняної політичної регіоналістики в контексті зазначених трендів та як галузі наукового знання.

Social and political challenges facing Ukraine after the Revolution of dignity, processes of regionalization and decentralization of European research actualized in political Regional studies. Regions in the EU has in fact become the basic structures of European political and economic space in the context of the philosophy of «Europe of Regions». Obviously, the Ukrainian political science must not stand by these trends pan and actively accompany this general trend of spatial structures. For balance and stability of the country depends on the regional structure, adequacy of political and socio-economic development. In this context it is particularly topical issue is the balance in the relations between the «center-regions» regulation is carried out by centralized and decentralized mechanisms. Accordingly, the purpose of the article is analysis of domestic political of regions in the current development of the state in the context of modern trends of regionalism. The article analyzes the domestic political status of regions in the context of the current complex processes of constitutional reform, decentralization of power and territorial reform. It is noted that areas related to the political-spatial system, acting as a kind of political system is not sufficiently developed. As a result, regional issues considered most economists or geographers, and the main thrust of Political Studies focused on the analysis of regional electoral processes and regional elites. This state of the domestic political concern of regions as administrative and territorial reform one of the main areas involve drastic changes is the system of public authorities at regional level. All this adversely affects the development of regional theory and practice of regionalism, as evidenced by the extremely inconsistent regional policy, the complexity and ambiguity of tragic political and legal processes: the Russian occupation of Crimea, the self-proclamation of the so-called Donetsk People’s Republic (DNR) and Luhansk People’s Republic (LNR). It is noted that the problem of disintegration of the Ukrainian society since independence have not been solved. Under regional theory should offer the best answer to this challenge. In particular, what model of government will help curb the centrifugal tendencies, strengthening integrity and thus provide an effective model of public administration and democracy. Given the tragic events that occurred in Ukraine in 2014–2017 years, to administrativeterritorial reform on the basis of administrative regionalism became impossible. Only with the use of policy instruments regionalization return of the Crimea and Donbas be real. It is noted that the political regionalism hides significant political risks versus administrative, including uncertainty about the future prospects of devolution trends. In this regard, notes that the learning experience of European countries, we should not idealize him and mindlessly trace unconditionally perform tips and suggestions of foreign politicians and experts (especially in the federalization). After these reforms, most EU countries carried out under conditions which significantly different from the current Ukrainian. It is also necessary to take into account national specifics, which differs significantly from European and neighboring countries geographic presence aggressor who provokes and supports separatist movements in Ukraine.
Ukrainian political regionalism in context of contemporary social and political challenges
Keywords: політична регіоналістика; регіоналізм; регіоналізація; регіон; децентралізація; political regional studies; regionalism; regionalization; region; decentralization